Fungos em rochas de ecossistemas extremos: taxonomia, diversidade, bioprospecção de metabólitos bioativos e uso como modelos em estudo de astrobiologia - Vivian Nicolau Goncalves (2015)
Some ecosystems are known as extreme due to different characteristics from those found in environments where most organisms are able to survive. Life in these ecosystems is often dominated by microorganisms, which are called extremophiles. In this condition, the rock 5 surface is often considered an extreme ecosystem due to it high or low temperatures, water activity fast changes and high UV radiation. Thus, this study aimed to evaluate the diversity of the fungal community associated with rocks present in extreme ecosystems, its capability to produce prototypes of bioactive metabolites, and use it as a model for astrobiology studies. Samples of Altitude Field rocks of Brazil, Atacama Desert and continental Antarctica 10 were collected and processed. One rock gram of each sample was pulverized, solubilized and plated on four different culture media (YM, MYEA, DG18 and DRBC). After processing, were obtained a total of 444 fungal isolates, been 292 (255 filamentous fungi and 37 yeasts) of Altitude field rocks, 81 filamentous fungi of the Atacama Desert and 71 (54 filamentous fungi and yeasts 17) of the Antarctic continent. Most of the isolates were identified in the 15 phylum Ascomycota and the class with greatest abundance was Eurotiomycetes. Taxa present in greater abundance in the Altitude Field of Serra of Caraça were Arthrocatena sp., Cladophialophora sp., Devriesia sp., Herpotrichiellaceae sp., Neophaeothecoidea sp., Paraconiothyrium sp. 1, Pezizomycotina sp. 1, Pseudotaeniolina sp., Teratosphaeriaceae sp.. Both in Atacama Desert and continental Antarctica genus Cladosporium and Penicillium 20 were isolated with the highest density, wich were the only cosmopolitan genera common to all study sites. The greatest scores of richness (Margalef) and diversity (Fisher) were obtained from the community of rock fungi of Altitude field, while the lowest were found in continental Antarctic. Regarding the Simpson index, the lowest value was also found in the community of rocks from Antarctic continent, while other communities had the same index 25 (0.96). Through similarity coefficients (Sorensen and Bray-Curtis), fungal communities of the Atacama Desert and Antarctic continent were the most similar. Considering density of taxa obtained through cultivation techniques, sampling effort carried out in all areas of collections showed to have been sufficient to achieve full diversity in rocks sampled. The fungi obtained from rocks were grown and their crude extracts tested in different biological assays to detect 30 metabolites with antimicrobial, antitumor, antiviral and antiparasitic activity. Of the extracts tested, 6.7% were active agaisnt at least one of the targets used. The isolate obtained from Atacama Desert rocks, Penicillium chrysogenum UFMGCB 8074, active against Candida albicans (MIC = 62.5 µg/mL) and tumor cell MCF-7, was selected for bioassay-guided fractionation. At the end were identified the substance ergosterol substance 5,8-35 endoperoxide, with activity against Staphylococcus aureus MRS (IC50 = 13.74 µg/mL) and linoleic and á-linolinic fatty acids, the latter being active against Cryptococcus neoformans (MIC = 10 µg/mL). From the active extracts Acremonium sp. UFMGCB 7138 (MIC = 125 µg/mL against the fungus Cladosporium shaerospermum) obtained from Brazil Altitude fields and Penicillium cf. coffeae UFMGCB 100021 (MIC = 125 µg/mL against C. albicans) was also possible to identify the fatty acids: palmitic, stearic, oleic and linoleic, in both and 5 pentadecanoic and heptadecanoic only in Acremonium sp. UFMGCB 7138. Among the yeasts isolated from rocks of continental Antarctica, wich were tested in astrobiology experiments, Rodothorula mucilaginousa AN6ADG-1 showed no significant loss of viability, even after exposure to UV-C and environmental UV, as well as in culture media with up to NaCl 2M. From the results obtained in this study, We can conclude that this work contributed 10 to a better understanding of the fungal community present in rocks of ecosystems studied, especially considering the pioneering study with samples from Brazil Altitude fields and the Atacama Desert. Bioprospecting results and chemical study of bioactive extracts demonstrated that community fungi present in rocks from ecosystems sampled can be a source of bioactive substances producing species. Furthermore, within fungal community 15 that live in rocks from extreme ecossytems may also contain fungi eukaryotes models for studies of life out of the planet